PSYCHOLOGICAL MECHANISMS OF IMPROVING TEACHING BASED ON INFORMATION-LOGICAL MODELING - Okbaeva Nilufar Urakovna (Modern American Journals, 2025)
Teaching based on information-logical modeling serves as an important psychological mechanism in developing students’ cognitive, logical, and algorithmic thinking skills in the modern educational process. This approach, grounded in the cognitive development theories of scholars such as Piaget and Vygotsky, activates students’ mental operations such as comparison, classification, reasoning, and decision-making. Through the use of If–Then schemes, flowcharts, and conceptual maps, conditional, step-by-step, and abstract thinking are effectively formed. Moreover, modeling enhances attention and memory processes while fostering competencies in data analysis, information retrieval, and decision-making. By stimulating metacognitive thinking, soft skills, and independent reasoning, this methodology transforms education from a purely knowledge-transmitting process into a thinking-enhancing one. As a result, students acquire competencies in working with complex information, applying algorithmic approaches, and mastering new knowledge through analytical processes.
Keywords: Information-logical modeling, cognitive psychology, logical thinking, algorithmic approach, metacognitive thinking, educational process, soft skills, mental operations, flowchart, conceptual map.